x - y = 2 4x - 3y = 11. Using Elimination method, eliminating x, multiply equation (i) by 4. Because of the 4 in the second equation. x - y = 2 ... (x4) 4x - 3y = 11. 4x - 4y = 8 4x - 3y = 11. The first minus the second. (4x - 4x) -4y- -3y = 8-11 -4y + 3y = -3 -y = -3. Divide both sides by -1 y =3. Substitute this value into the very first equation x - y = 2, y = 3 x - 3 = 2 x = 2 + 3 = 5. Therefore x = 5, y = 3.

-4[x-y=2[ 4x-3y=11 -4x+4y=-8 0+y=3 y=3 now, i am going to find x value. put 3 on y value to get x value i want use easy way because x-y=2 is easy to get x value. x-3=2 x=2+3 x=5 right now, i am gonna check my answer if it's wrong i am going to take x-y=2 because its easy to check my answer x-y=2 x = 5, y=3 so i am gonna check it. 5-3=2 so the answer is x=5, y=3